"In Vivo" Effects of Lithium Sulphate on the Turnover of Rat Tissue Nucleotides. Issue 3 (1996) - Loghin Loghin, Felicia Felicia; Socaciu Socaciu, Carmen Carmen; Leucuta Leucuta, Sorin E. Sorin E.
Abstract : The effects of lithium sulphate following acute administration to Wistar rats - in therapeutic and toxic doses - were investigated, using as markers the levels and turnover of brain, kidney and liver nucleotides. Adenine- and guanine-dependent nucleotides were assayed concomitantly, using a high- performance liquid chromatographic method. Following acute administration, lithium's effects on 3', 5'- cAMP levels were more significant at hepatic and cerebral level, in a dose-dependant manner. The effect on 3', 5'-cGMP had tissue specificity and was not dose-dependant. It might be possible that 3', 5'-cGMP is a better indicator of lithium toxicity than 3', 5'-cAMP.